The Influence Of Work Climate On Teacher Job Satisfaction At Skye Digipreneur Vocational School Bandung - zafira, Alifia; Pramanik, Nuniek Dewi (Pascasarjana STIE Miftahul Huda, 2025)
This study aims to determine the effect of work climate on teacher job satisfaction at SMK Skye Digipreneur Bandung. Work climate is measured through relationships between teachers, leadership, and communication, while job satisfaction is seen from comfort, appreciation, and opportunities for development. The study used a quantitative method with a descriptive approach. The sample of the study was all 60 teachers, with a saturated sampling technique. The research instrument was a Likert scale questionnaire, which was tested for validity and reliability, then analyzed using simple linear regression with the help of SPSS. The results showed that work climate has a positive and significant effect on teacher job satisfaction. The regression coefficient value of 0.702 with a significance of 0.000 (<0.05) proves that the better the work climate, the higher the teacher job satisfaction. The coefficient of determination (R²) of 0.840 indicates that 84% of the variation in job satisfaction can be explained by work climate, while the remaining 16% is influenced by other factors. These findings emphasize the importance of supportive leadership, effective communication, and harmonious working relationships in improving teacher satisfaction. It is recommended that further research involve a larger number of respondents and consider other variables that can influence teacher satisfaction. Work.